ANALISIS LAJU PERTUMBUHAN SUMBER DAYA PETANI PADA SEKTOR PERTANIAN PROVINSI SUMATERA SELATAN (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2019)
Analyze the rate of growth of farmer resources in the agricultural sector of South Sumatra Province. This research was conducted in South Sumatera Province. Location determination is done purposively where the Province of South Sumatera is a province that most of its inhabitants are searching for agriculture sector and its people work in agriculture sector. The method used in this research is literature study method. The type of data used in this research is secondary data (time series). Taking into account the availability of data, this study uses data for 10 years (2006-2015). Data taken from the Central Bureau of Statistics is data on the number of people working in the agricultural sector in South Sumatra Province. The results of this study indicate that (1) there is a decrease in the resources of farmers in South Sumatera Province with a growth value of -1.33%, this means a decline in the growth of agricultural resources by -1.33% from 2006 to 2015. ( 2) the growth of farmers resources of South Sumatera Province in 2018 as much as 1,628,401, in 2019 as much as 1,592,104 and by 2020 the growth of farmers resources in South Sumatra Province is predicted to grow by 1,555,807.